The effect of ESG disclosure and PROPER rating on corporate financial performance with GCG as a moderating variable in Indonesia’s energy sector - Vennesa Aisah Mulyana; Sugeng Sugeng (Institute of Accounting Research and Novation (IARN), 2026)
The paradigm of corporate performance assessment has undergone a fundamental shift, moving beyond narrow financial metrics toward comprehensive sustainability indicators. This study investigates the influence of Environmental, Social, and Governance (ESG) disclosure and PROPER (Program Penilaian Peringkat Kinerja Perusahaan dalam Pengelolaan Lingkungan Hidup) environmental rating on corporate financial performance, with Good Corporate Governance (GCG) serving as a moderating variable. Employing a quantitative-causal research design with balanced panel data drawn from 25 energy sector companies listed on the Indonesia Stock Exchange (IDX) over the period 2020–2025 (150 firm-year observations), this study applies Fixed Effect Model (FEM) panel regression and Moderated Regression Analysis (MRA) with mean-centered interaction terms. Empirical results demonstrate that ESG disclosure exerts a statistically significant and positive effect on Return on Equity (ROE) (β = 0.3387; p = 0.0028), consistent with the predictions of stakeholder theory and signaling theory. PROPER environmental rating, however, yields no statistically significant direct effect on ROE (β = 0.0071; p = 0.8657), attributable to constrained rating dispersion within the sample and the long-horizon reputational nature of government-mandated environmental signals. Critically, GCG significantly amplifies the ESG–ROE relationship through a complementary moderation mechanism (β = 6.4801; p = 0.0002), indicating that robust governance structures substantially enhance the value relevance of sustainability disclosures. The model demonstrates strong explanatory power (Adjusted R² = 0.6825; Durbin-Watson = 2.0028), advancing theoretical understanding of sustainability governance performance dynamics within the Indonesian energy sector.